PRO KONTRA RANCANGAN KITAB UNDANG-UNDANG HUKUM PIDANA TAHUN 2017 - Dahwir, Ali (Solusi, 2020)
This paper discusses the pros and cons of ratification of the 2017 Draft Criminal Code. The purpose of this research is to find out and analyze what is the basis of the conflict so that the 2017 Draft Law Book will not be ratified in 2019. Discussions on the problems that have been determined are discussed using normative legal research methods, explanatory with primary, secondary and implied legal material. The approach used is a concept approach, history and approach to the law. The rejection from the public for the ratification of the 2017 Draft Criminal Code is due to a lack of understanding of the substance of the articles which are considered controversial. In addition, according to some experts in the Draft Book of the Criminal Law, it is regulated again about what actually has been regulated in a special criminal law. This makes it possible for the law to be vulnerable to misuse in its application. Actually, if you read more carefully the Draft Book of the Criminal Law, new rules will be found that have been adapted to the values ​​contained in the Pancasila principles. In the end it would be better if the Draft Book of the Criminal Law was passed into law.